Effects of Energy Prices on Environmental Pollution: Testing Environmental Kuznets Curve for Algeria - Layachi, Ouarda Belkacem (International Journal of Energy Economics and Policy, 2019)
The current study is primarily motivated in testing Environmental Kuznets Curve (EKC) framework by including energy prices along with output growth. In addition, the current study is also important for analyzing the impact of energy prices by testing the effects of three different fuel prices. They include crude oil prices, natural gas prices and heating oil. The data is gathered from the period of 1980-2017. The results of ARDL confirm that economic growth has a positive and significant impact on carbon emission in Algeria. On the other hand, all energy prices (oil prices, heating oil and natural gas prices) confirm a negative and significant impact on carbon emission in Algeria. The results of ARDL also confirm a presence of U-Shaped EKC curve in the Algeria. The results VDM have confirm a bi-directional causal relationship between oil prices and carbon emission, however we found a unidirectional causal relationship from heating oil prices to carbon emission and no causal relationship between natural gas prices and carbon emission in Algeria. Keywords: Oil prices, natural gas prices, heating oil prices, Algeria. JEL Classification: E31, Q5, Q56 DOI: https://doi.org/10.32479/ijeep.8312